The Alternative Methods of Recording, Recognizing, and Reporting Tether (Usdt) Crypto Assets Based on Ifrs Standards - Lolang, Vito Sahaya Immanuel; Irianto, Gugus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to identify the most relevant alternative accounting treatment for the recording, recognising, and reporting the cryptocurrency, Tether (USDT), a fiat-backed stablecoin, by IFRS standards. The research method utilised is a literature review of relevant articles published between 2018 and 2024, obtained through Google Scholar, which were subsequently analysed. The findings suggest that the most suitable approach for the recording, recognition, and reporting of the cryptocurrency, Tether (USDT), is through the application of IFRS IAS 2 about inventory. Dance to IAS 2 (PSAK 14).